1972
DOI: 10.1038/icb.1972.69
|View full text |Cite
|
Sign up to set email alerts
|

Potassium Tolerance in Rats

Abstract: Summary A state of potassium tolerance has been produced in rats by the administration of a high potassium diet. Tolerant rats had an increased survival when subjected to continued potassium loads and an enhanced ability to excrete potassium. Tolerant animals also had a lower plasma potassium concentration than controls when subjected to similar potassium loads. Increased urinary1excretion of potassium in tolerant animals was not dependent on sodium excretion but was accompanied by a reduced stool sodium/potas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1975
1975
2013
2013

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…Alexander and Levinsky [1968] were able to confirm that in the potassium-adapted rat, increased urinary excretion of potassium could occur but extra-renal uptake of the ion was also increased and the adaptation was suggested to be due to enhanced potassium uptake by more than one tissue in response to chronically high mineralocorticoid levels. In a later study the increased ability of potassium-tolerant rats to excrete potassium in the urine was associated with evidence of increased mineralocorticoid activity but the extra-renal component of potassium adaptation was not confirmed [Adam and Dawborn, 1972]. The changing response of the adrenalectomized sheep to the infusion of potassium had a number of features which were similar to potassium adaptation in the rat and dog.…”
Section: Discussionmentioning
confidence: 55%
“…Alexander and Levinsky [1968] were able to confirm that in the potassium-adapted rat, increased urinary excretion of potassium could occur but extra-renal uptake of the ion was also increased and the adaptation was suggested to be due to enhanced potassium uptake by more than one tissue in response to chronically high mineralocorticoid levels. In a later study the increased ability of potassium-tolerant rats to excrete potassium in the urine was associated with evidence of increased mineralocorticoid activity but the extra-renal component of potassium adaptation was not confirmed [Adam and Dawborn, 1972]. The changing response of the adrenalectomized sheep to the infusion of potassium had a number of features which were similar to potassium adaptation in the rat and dog.…”
Section: Discussionmentioning
confidence: 55%
“…After a chronic increase in dietary potassium intake, a sequence of adaptive changes takes place in the kidneys that lead to the more effective and enhanced excretion of potassium after an acute potassium load (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). This response, called potassium adaptation, is associated with a sharp elevation of plasma aldosterone levels and with an increase in potassium secretion by the initial collecting, cortical collecting, and medullary collecting tubules (1-3, 11, 12, 17-21).…”
Section: Introductionmentioning
confidence: 99%
“…The experiments were carried out in conscious, unrestrained animals after a 16-20 h fast. At this time there is no detectable difference in plasma electrolyte status of CK and HK rats (Adam & Dawborn 1972).…”
Section: Methodsmentioning
confidence: 91%
“…Whilst there is some evidence for an adaptation in K excretion independent of adrenal steroids (Wingo et al 1982), prior adrenalectomy obliterates most of the adaptive process (Adam & Dawborn 1972;Adam, Goland & Wellard 1984). More recently we have shown that the greater part of the kaliuretic adaptation relates to adrenal steroids, both mineralocorticoids and glucocorticoids (Adam et a/ 1984).…”
Section: Introductionmentioning
confidence: 94%